2021
DOI: 10.1002/wer.1601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluoride adsorption in solution by synthetic Al2O3/CeO2: A fixed‐bed column study

Abstract: A highly efficient fluoride adsorbent Al2O3/CeO2 was synthesized in this work and used it to fluoride removal in the fixed‐bed adsorption through changing the different experimental conditions (influent F− concentration, flow velocity, and bed heights). The adsorption capacity was 9.72 mg/g. In addition, the Adams–Bohart and Thomas models were used to fit and evaluate the column breakthrough curve of fluoride removal process by Al2O3/CeO2, and the correlation coefficients (R2) of the Thomas model were close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…CF bonds appeared in the spectra of C 1s (Figure 10b) and F 2p (Figure 10d), 35,36 demonstrating that part of PTFE was transferred to the dual surface. In addition, peaks of metal fluorides (MF n ) (M = Fe, Al, et al), FeF 3 , FeF 2 and Al‐F appeared in the XPS spectrums of F 2p, 37 Fe 2p 38 and Al 2p, 39 respectively (Figure 10d–f), which was attributed to the tribochemical reactions taking place between PTFE and metal dual ball or Al powders. During sliding friction, the CC or CF main chain bonds of PTFE will break, under the action of oxygen and water molecules in the atmosphere, carboxyl groups were formed, and the carboxyl groups can chelate to the steel ball or Al powders, 37,40 thereby forming a robust tribofilm.…”
Section: Resultsmentioning
confidence: 97%
“…CF bonds appeared in the spectra of C 1s (Figure 10b) and F 2p (Figure 10d), 35,36 demonstrating that part of PTFE was transferred to the dual surface. In addition, peaks of metal fluorides (MF n ) (M = Fe, Al, et al), FeF 3 , FeF 2 and Al‐F appeared in the XPS spectrums of F 2p, 37 Fe 2p 38 and Al 2p, 39 respectively (Figure 10d–f), which was attributed to the tribochemical reactions taking place between PTFE and metal dual ball or Al powders. During sliding friction, the CC or CF main chain bonds of PTFE will break, under the action of oxygen and water molecules in the atmosphere, carboxyl groups were formed, and the carboxyl groups can chelate to the steel ball or Al powders, 37,40 thereby forming a robust tribofilm.…”
Section: Resultsmentioning
confidence: 97%
“…The continuous xed bed column potentiality was evaluated by the breakthrough time period and removal quantity given in Eq. 1 (Chen et al 2021;Tor et al 2009). To know the effective efforts of the xed bed glass column systems applying various easy numerical models were succeeded.…”
Section: Fixed Bed Column Studiesmentioning
confidence: 99%
“…Arti cial neural network (ANN) is a powerful prediction tool for the identi cation of the relevant parameters and their correlation relationships are very complex. Removal of toxicants from aqueous solutions using different prediction models has been used current time by numbers of researchers (Chen et al 2021;Wan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, activated alumina has a large specific surface area and a rich aperture structure. It is the most common kind of fluoride-removal adsorbent [28,29]. Relevant studies have shown that Fe is a typical transition metal, widely distributed in environmental minerals.…”
Section: Introductionmentioning
confidence: 99%